Reactualization of the Muhammadiyah Da'wah Movement in Responding to the Covid-19 in Providing Peace - Surni Kadir; Hamdi Rudji; Nurhayati Nurhayati; Nuranisa Nuranisa; Asnidar Asikin (IJISH (International Journal of Islamic Studies and Humanities), 2022)
This study aims to analyze the reactualization of the role of Muhammadiyah's da'wah in responding to the COVID-19 pandemic in providing a sense of calm for the congregation of Palu City. The method in this study is carried out by field and literature studies from a number of books, relevant journals and data obtained through literature studies are used to make a descriptive analysis of the focus of the study. The results of this study are divided into two parts; first, the actualization of the role of Muhammadiyah's da'wah in Covid-19 is to establish the Muhammadiyah Covid-19 Comment Center (MCCC), which is tasked with dealing with Covid 19. Muhammadiyah views active efforts to prevent covid 19 as a form of worship that has the value of jihad and is part of the amar ma’rūf nahi munkar. Second, Muhammadiyah chose the path of da'wah bi al-ḥikmah, using the pillars of revelation and scholarship, then set off a fatwa issued by the Tarjih Council as a guide for worship during the covid 19 pandemic, so Muhammadiyah's da'wah steps During the COVID-19 pandemic can have implications for peace for the community.